Pyroelectric energy harvesting using automobile exhaust emission. (2022) - Wazeer, Adil; Srikanth, K.S.; Mathiyalagan, P.; Vidya, Shrikant
Abstract: The study presents the pyroelectric performance improvement by employing exhaust emissions from automobiles. Electric outputs through the material BaSn0.05Ti0.95O3 are recorded after subjecting the surface of the sample for heating under infrared (IR) lamp and flowing water. The thickness of the automobile exhaust ink was nearly 35 µm on the sample surface. Observations show significant improvements with open circuit voltage increase to five times, electric current enhances upto six times across the resistor of 10 Ω and nearly 17 times increment in energy harvested. Peak values of open circuit voltage obtained were 0.3 and 1.2 V for uncoated as well as coated samples respectively. The electric current for the heating & cooling cycle represents peak value of 1.47 µA when compared with uncoated sample with a value of 0.24 µA. Moreover, energy stored across capacitor of10 µF founds an increment from 1.4 µJ for uncoated sample to 23.10 µJ for coated sample. The study proposes effective utilization of harmful automobile exhaust and harvesting of energy for low power electronics. Therefore this study systematically investigates the pyroelectric energy potential of BaSn0.05Ti0.95O3 ceramics by using automobile emission and compares it with similar class of materials.